Coupled CFD–DEM Investigation of Erosion Accompanied by Clogging Mechanism under Different Hydraulic Gradients. (January 2023) - Mu, Linlong; Zhang, Peiyun; Shi, Zhenhao; Huang, Maosong
Abstract: Soil internal erosion refers to any process that the finer grains are eroded from the matrix of coarser grains due to seepage. A coupled computational fluid dynamics and discrete element method (CFD–DEM) analysis of internal erosion is conducted on bimodal soils. The coupled influences of hydraulic gradient i and fine content Fc on different domination process of internal erosion is investigated. It is found that the erosion degree does not always increase as i increases for "underfilled" soil (e.g. Fc = 10 % and Fc = 20 %), there is a hydraulic gradient threshold ith above which local particle clogging plays a dominant role, resulting in a smaller erosion degree instead, the ith is larger for larger Fc, when Fc is equal to 10, the ith is 2 or less, while ith is 4 for the soil with a fine content of 20 %. For "transitional" soil (e.g. Fc = 30 %), no obvious clogging domination under larger i is observed. The mechanism is revealed through both macro- and microquantity perspectives. It is found that local clogging is formed by particle bridge formation under larger i values. These findings are highly significant for further understanding the influence of i on the erosion process and establishing the erosion law.